Pengembangan Media Game Edukasi Materi Aljabar Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Kelas VII SMP Ma’arif NU 1 Bumiayu - Faskha, Muhammad Kemal; Kumala, Fitria Zana (UM Purwokerto Press, 2025)
This study aims to develop and examine the effectiveness of an educational game as a learning medium for mathematics, specifically on algebra material, in improving the mathematical problem-solving abilities of seventh-grade students. The research method used was Research and Development (R&D) with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of two classes: the experimental class, which used the educational game, and the control class, which used conventional lecture methods. The validation results show that the developed educational game has a high level of validity. Validation by material experts obtained an average score of 80% (valid), while validation by media experts reached 88.5% (very valid). The attractiveness test involving teachers and students showed highly positive results, with an average score from mathematics teachers of 94.3%, a small group trial result of 90.2%, and a field trial result of 84.71% (all categorized as very attractive). The effectiveness of the game was analyzed using the N-Gain test. The results showed that the average N-Gain in the experimental class was 0.73 (high category), while the control class only reached 0.46 (medium category). This indicates that using educational games is more effective in improving students' mathematical problem-solving abilities than conventional lecture methods. Students who used the educational game demonstrated improvement in all indicators of problem-solving ability, such as understanding the problem, planning a solution, carrying out the plan, and reviewing the result. Therefore, the educational game developed in this study is proven to be valid and effective as a learning medium for mathematics, particularly in algebra. The use of educational games can serve as an innovative alternative to enhance students' mathematical problem-solving skills.